Breaking new ground in heart failure management: novel therapies and future frontiers - Arbab Khalid; Paulette Rodriguez; Vasiliki Tasouli-Drakou; Abu-Bakr Ahmed; Spencer Thatcher; Jasmine K. Dugal; Aditi Singh (Frontiers in Cardiovascular Medicine)
Heart failure (HF) management is advancing in the field of cardiology, driven by the increasing availability of progressive medications. Emerging pharmacological therapies in heart failure management include SGLT-2 inhibitors, ARNI, Vericiguat, and Omecamtiv. Other novel therapies that are changing the scope of HF management include IV Iron therapy and new antifibrotic agents, such as pirfenidone and pamrevlumab. With groundbreaking approaches such as gene and stem cell-based therapies, the possibilities include gene editing and RNA-based therapies. This article contrasts novel HF therapies against previously used therapies, highlighting their mechanism of action, clinical efficiency, and relevant clinical trials. Additionally, the limitations and challenges associated with the emerging therapies will be discussed. Overall, this literature review aims to provide a comprehensive understanding of how these therapies are transforming the management of HF and related cardiomyopathies.